Work-Family Conflict of Women Entrepreneurs and Women Employees - Cicilia Larasati Rembulan; Kuncoro Dewi Rahmawati; Febe Yuanita Ratna Indudewi (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
The aim of this study was to discover differences in work-family conflict among women who work as employees and women who worked as entrepreneurs. The samples of this re-search were 189 women (98 employees and 91 entrepreneurs). This quantitative com-parative design used an incidental sampling technique. The measuring instrument was the work-family conflict (WFC) translated from Greenhaus and Beutell. The data collected was analyzed using Mann Whitney-U Test. The results show no difference in WFC among women who work as employees and women as entrepreneurs. However, the data shows that the majority of entrepreneur women has very low WFC in all aspects (time, strain, and behavior), while women who work as employees tend to have medium WFC. The results of cross tabulation show that there are indications of an association between revenue and WFC (time and strain aspects) in employee respondents. While the entrepreneur women show indication of an association between the ages of marriage, and duration of work with WFC.